Impact, Implications, Challenges of Accelerating Maternal Mortality Rates in Indonesia - Suparji Suparji; Heru Santoso Wahito Nugroho; Sunarto Sunarto; Abdul Latif; Agus Sarwo Prayogi (Knowledge Dynamics, 2024)
This article discusses the impacts, implications and challenges of accelerating maternal mortality rates in Indonesia. Maternal Mortality Rate (MMR) in Indonesia is still a serious public health problem. MMR in Indonesia shows a downward trend throughout the 1991-2015 period. However, in 2012 the infant mortality rate increased again and then fell in 2018. Even though it shows a decline, the MMR in Indonesia is still relatively high and still above the MDGS target of 102 per 100,000 live births. MMR in Indonesia in 2021 compared to 2020. The impact of a high MMR is a decline in the productive and competitive workforce, a decline in social welfare and poverty, a decline in life expectancy and quality of life in society, a decline in fertility rates and population growth, which can affect the demographic structure and demographic bonus. and declining reproductive and nutritional health status of women and children. Meanwhile, the implications arising from a high MMR are implications in terms of health, social, economic and development status. The challenges faced by Indonesia in reducing MMR are the low health budget allocation, the lack of health facilities and personnel, low access to PONED (Basic Emergency Neonatal Obstetric Services) and PONEK (Comprehensive Emergency Neonatal Obstetric Services) facilities, high disparities in socio-economic levels, and low awareness and healthy living behavior in the community. The conclusion of this short article about the maternal mortality rate in Indonesia is that the maternal mortality rate in Indonesia is still high and has not yet reached the Sustainable Development Goals (SDGs) target set by the UN, namely 70 per 100,000 live births in 2030. This article recommends Reducing MMR requires comprehensive and collaborative efforts from all parties, including central and regional governments, health institutions, civil society organizations, academics, media and society.